About the Normative Regulation and Fostering the Methodology Culture of Pedagogical Research Staff - V. I. Zagvyazinsky; A. F. Zakirova (Russian State Vocational Pedagogical University, 2015)
The paper discusses the reorganization problems regarding the educational research sphere and based on the draft of the Modernization Concept of the Scientific Staff Higher Attestation System in the Russian Federation, which recommends some preventive measures to counteract the research imitations, incorrect borrowing and paraphrasing of well-known ideas. The first, or the normative regressive trend, implies the prescribed procedure frames and rigid regulatory forms concerning the publications, scientific reports and defense of the theses. The authors regard most of the above measures as necessary for filtering out the plagiarism and superficial works. However, the other trend - more important in their opinion - implies the development of the research methodology culture. The paper reveals the ten-year-experience of the Interregional Ural- Siberian Seminar on the Practical Methodology of Socio-Pedagogic Research, organized in Tumen State University. The twenty sessions of the given seminars included the lectures by leading specialists, master-classes and role plays (mini research defense), and involved all the research stages: selecting a theme, defining a research problem, and finally, a report preparation and presentation to the attestation comity. The authors make a conclusion concerning the educational research regulations aimed to balance the administrative statutory measures with systematic development of methodology culture and fostering the researchers' social responsibility and creativity.